IMAGES, RELICS AND DEVOTIONS AT THE COLEGIO MÁXIMO DE SAN MIGUEL`S CHURCH: ICONOGRAPHY, RELATIONS AND FUNCTIONS (SANTIAGO DE CHILE, SIGLO XVIII) - Schenke Reyes, Josefina (Revista de Historia Social y de las Mentalidades, 2024)
This paper deals with the worship objects and  cultual practices that or ganize the inner space  of the Colegio Máximo de San Miguel’s church  (Santiago de Chile) in the course of the  x VIII  century, focusing on those sacred objects which  are opened to the faithful and reserved not  only to the clergymen. This analysis brings out  the cultual specificity of each of the chappels,  highlighting their devotional coherence as well  as the equilibrium they manage to preserve  between different types of images and cults. In  this way, an strategy aimed at reinforcing the link  which connects the Company and its saints to the  universal Church is uncovered, one of whose main  features includes the use of relics as elements  underscoring the above mentioned link.
Keywords: Society of Jesus; Devotions; Images; Relics; XVIII century; Santiago of Chile